2000
DOI: 10.1002/(sici)1099-1263(200001/02)20:1<81::aid-jat629>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive effects of hexachlorobenzene in female rats

Abstract: Hexachlorobenzene (HCB) is a polyhalogenated aromatic hydrocarbon widely distributed in the environment. In animal testing, HCB has been shown to be a reproductive toxin. Previous investigations of the effects of HCB on ovarian function have yielded equivocal results. Thus, the effects of chronic administration of HCB (1 g kg−1 body wt.) on the ovary and pituitary hormone levels, hepatic and uterine oestradiol receptors, ovarian histopathological changes and oestrus cycle characteristics were investigated in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…These results are in line with the hypothesis that HCB might protect against gynecomastia by its inhibiting effect on aromatase. Our findings are consistent with observations indicating that HCB lowered estradiol levels in female rats (Alvarez et al, 2000) and in monkeys (Foster et al, 1995). The positive relation between lead and the occurrence of gynecomastia may be explained by the xenoestrogenic properties of lead (Martin et al, 2003).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in line with the hypothesis that HCB might protect against gynecomastia by its inhibiting effect on aromatase. Our findings are consistent with observations indicating that HCB lowered estradiol levels in female rats (Alvarez et al, 2000) and in monkeys (Foster et al, 1995). The positive relation between lead and the occurrence of gynecomastia may be explained by the xenoestrogenic properties of lead (Martin et al, 2003).…”
Section: Discussionsupporting
confidence: 93%
“…In pubertal male rats, p,p 0 -DDE inhibits androgen binding to the androgen receptor, androgen-included transcriptional activity and androgen action (Kelce et al, 1995). Hexachlorobenzene (HCB) was reported to significantly decrease uterine nuclear estrogen receptor levels, which may alter ovarian function and menstrual cycle characteristics (Foster et al, 1995;Alvarez et al, 2000). Cadmium was observed to mimic the effect of estrogen by activating estrogen receptor-a and to block binding to the androgen receptor (Stoica et al, 2000;Martin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…PCBs are known to have estrogenic, anti-estrogenic and antiandrogenic activities (Bonefeld-Jorgensen et al, 2001); p,p'-DDE was reported to have antiandrogenic properties (Kelce et al, 1995); HCB was reported to affect oestradiol levels in animals (Alvarez et al, 2000;Foster et al, 1995) and to interact with hormone receptors (Li et al, 2008); cadmium was observed to be able to interact with both oestrogen and androgen receptors (Stoica et al, 2000;Martin et al, 2002); lead was reported to have xenoestrogenic activity (Martin et al, 2003) and to affect pubertal development in girls (Selevan et al, 2003); polycyclic aromatic hydrocarbons were reported to affect development (Choi et al, 2006) and display as well AhR as estrogen receptor-mediated activity (Hilscherova et al, 2000). We wanted to test the hypothesis that low differences in levels of internal exposure (such as these occurring in the general population in Flanders) to endocrine disrupting substances result in differences in body size parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The pollutants that were studied are known to have endocrine-disrupting properties. PCBs were reported to have estrogenic, anti-estrogenic and anti-androgenic activities (Bonefeld-Jorgensen et al, 2001;Hansen, 1998); p,p 0 -DDE is known to have anti-androgenic properties (Kelce et al, 1995); hexachlorobenzene (HCB) was reported to affect oestradiol levels in animals (Alvarez et al, 2000;Foster et al, 1995); cadmium was observed to be able to interact with both estrogen and androgen receptors (Martin et al, 2002;Stoica et al, 2000); lead was reported to have xeno-estrogenic activities (Martin et al, 2003) and to affect pubertal development in girls (Selevan et al, 2003;Wu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%